Prophetic-Based Character Education Management in Improving the Quality of Graduates: (A Multi-Site Study at Pondok Pesantren Pembangunan Al Fattah Kikil and Pondok Pesantren Pembangunan Al Fatahiyah) - Alif Fatkhur Rohman; Akhyak Akhyak; Asrop Safi’i (International Journal of Islamic Educational Research, 2026)
This dissertation, titled "Prophetic-Based Character Education  Management in Improving Graduate Quality (A Multi-Site Study at MA  Pembangunan Pondok Pesantren Al Fattah Kikil Pacitan and MA Pondok  Pesantren Al Fattahiyah Boyolangu Tulungagung)," The research questions in this study are: 1) How is humanistic-based  character education management applied at MA Pembangunan Pondok  Pesantren Al Fattah Kikil Arjosari Pacitan and MA Pondok Pesantren Al  Fattahiyah Boyolangu Tulungagung to improve graduate quality? 2) How is  liberation-based character education management implemented in  improving graduate quality at the same institutions? 3) How is  transcendence-based character education management applied at these  institutions to enhance graduate quality?The findings related to humanistic-based character education  management in improving graduate quality at MA Pembangunan Pondok  Pesantren Al Fattah Kikil Arjosari Pacitan and MA Al Fattahiyyah Boyolangu  Tulungagung include: 1) annual madrasah meetings, 2) explicit integration  of prophetic education in the 2013 curriculum, 3) integrated curriculum  design, 4) innovative teaching approaches, 5) collaboration with  parents/guardians, 6) adherence to madrasah education goals, and 7) FGD  on vision and mission. Findings related to liberation-based character education management  for enhancing graduate quality at both institutions include: 1) comfortable  and enjoyable classroom management, 2) prophetic, multimedia-based environment management, 3) social role management, 4) digital learning,  5) integration of character education into all subjects, 6) research-based  learning, and 7) literacy skills among the madrasah community. The research findings on transcendence-based character education  management in improving graduate quality include: 1) extracurricular  activities incorporating transcendence-based prophetic education, 2)  fostering transcendence-based prophetic character during learning  activities, 3) phased monitoring, 4) evaluation through activities, 5)  supervision involving extracurricular mentors, 6) establishment of  character education programs, 7) parental involvement, 8) home visits, 9)  extracurricular programs integrating prophetic education with social roles,  10) fostering social-role-based prophetic character in learning, and 11)  religious habituation programs.